2019
DOI: 10.1111/cogs.12789
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Language Experience Modulates Visual Attention to Visible Speech and Iconic Gestures During Clear and Degraded Speech Comprehension

Abstract: Visual information conveyed by iconic hand gestures and visible speech can enhance speech comprehension under adverse listening conditions for both native and non‐native listeners. However, how a listener allocates visual attention to these articulators during speech comprehension is unknown. We used eye‐tracking to investigate whether and how native and highly proficient non‐native listeners of Dutch allocated overt eye gaze to visible speech and gestures during clear and degraded speech comprehension. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 65 publications
7
48
4
Order By: Relevance
“…In occipital regions, we observed a stronger drive by the 68 Hz visual modulation signal when speech was clear than when speech was degraded. This is in line with previous eye-tracking work that demonstrated that when speech is degraded, listeners gaze more often to the face and mouth than to gestures to extract phonological information to aid comprehension (Drijvers, Vaitonytė, et al, 2019), as well as previous work that revealed that the amplitude of SSVEPs was enhanced by visual attention, irrespective of whether the stimuli were task-relevant (Morgan et al, 1996;Müller et al, 2006). Note that gestural information is often processed in the periphery of a listener's visual field (Gullberg & Holmqvist, 1999Gullberg & Kita, 2009).…”
Section: Clear Speech Enhances Visual Attention To Gestural Informationsupporting
confidence: 90%
“…In occipital regions, we observed a stronger drive by the 68 Hz visual modulation signal when speech was clear than when speech was degraded. This is in line with previous eye-tracking work that demonstrated that when speech is degraded, listeners gaze more often to the face and mouth than to gestures to extract phonological information to aid comprehension (Drijvers, Vaitonytė, et al, 2019), as well as previous work that revealed that the amplitude of SSVEPs was enhanced by visual attention, irrespective of whether the stimuli were task-relevant (Morgan et al, 1996;Müller et al, 2006). Note that gestural information is often processed in the periphery of a listener's visual field (Gullberg & Holmqvist, 1999Gullberg & Kita, 2009).…”
Section: Clear Speech Enhances Visual Attention To Gestural Informationsupporting
confidence: 90%
“…As such, perhaps the nonnative listeners at a low-intermediate level are still dependent on clear semantic meaning in gestures. By contrast, the studies by Dahl and Ludvigsen (2014) and Drijvers et al (2019a), who found positive effects of iconic gestures on recall and comprehension processes, recruited advanced learners and exposed them to referential gestures, whereas in the current study, the non-native listeners had a low-intermediate level and were exposed to nonreferential gestures.…”
Section: Discussioncontrasting
confidence: 70%
“…In a recent eye-tracking study, Drijvers et al (2019a) expanded upon these results. The authors presented native and highly proficient non-native listeners a set of Dutch verbs that were uttered either with or without gesture, and in clear and degraded speech.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Gestures are visual articulators and subject to visual processing. Although earlier research found that gestures can be processed peripherally and do not require direct visual attention (e.g., Gullberg andHolmqvist, 1999, 2006;Gullberg and Kita, 2009), recent evidence suggests that several factors might modulate how listeners allocate overt visual attention to gestures such as the comprehensibility of speech, and the native/non-native status of the listener (e.g., Drijvers et al, 2019). Future studies should address whether people with different visual-spatial vs. verbal abilities show differential overt visual attention to gestures and how this relates to individual differences in gesture processing (Wakefield et al, 2018).…”
Section: Discussionmentioning
confidence: 99%